IDENTIFIKASI PERILAKU SEKS BEBAS AKIBAT KONSUMSI MINUMAN BERALKOHOL PADA PENGUNJUNG REMAJA KELAB MALAM â€œXâ€ SEMARANG - Putra, Ardhianto Pradhana; Cahyo, Kusyogo; Widagdo, Laksmono (Fakultas Kesehatan Masyarakat, 2018)
At 2010 Indonesian consumption alcohol rate was 7.1 liter per year. Quoting from BKKBN at 2014 half of the urban girl dan 62,7% junior high school girl has give away their virginity. Quoting from the Journal of Addiction the alcohol consumption at spesific rate can lead to a risky sex. The purpose of this study is to identify free sex behavior due to alcohol consumption in nightclub visitors